Validation of the fault rupture-response spectrum analysis method for ordinary and seismically isolated bridges crossing strike-slip fault rupture zones. (15th December 2022) - Yang, Shuo; Mavroeidis, George P.; Tsopelas, Panos
Highlights: The FR-RSA method is adequate for the analysis of ordinary and seismically isolated bridges crossing strike-slip faults. The peak quasi-static response, r Q S F P, dominates the peak total response of ordinary straight bridges. The peak dynamic responses, r o F N and r o F P, constitute a significant portion of the peak total response of seismically isolated bridges. The FR-RSA method requires application of different damping ratios to the isolation modes and non-isolation modes of the seismically isolated bridges. The isolation modes and pier modes control the peak isolation displacements and peak pier drifts of the seismically isolated bridges. Abstract: The fault rupture-response spectrum analysis (FR-RSA) method approximates the peak response of bridge structures crossing strike-slip faults by superposing the peak quasi-static and dynamic responses in the fault-normal and fault-parallel directions. The first part of this article aims to further validate the accuracy of the FR-RSA method for estimating the peak response of ordinary bridges crossing strike-slip faults. This is achieved by comparing results obtained from the FR-RSA method against nonlinear response history analysis (NLRHA) for two ordinary straight bridges under different fault crossing conditions. The effects of modal combination rule and number of modes on the peak response of the considered ordinary bridges are also examined. The second part of the article investigates the adequacy of the FR-RSA method for estimating the peak response of seismically isolated bridges crossing strike-slip faults. This is achieved by considering two seismically isolated bridges along with different fault crossing angles, fault crossing locations, and input ground motions and by comparing results obtained from the FR-RSA method against NLRHA. This investigation involves examining the effects of modal combination rule, number of modes, damping ratio, and mode type on the peak response of the considered seismically isolated bridges. The analysis results indicate that the peak responses of ordinary and seismically isolated bridges computed from the FR-RSA method are in good agreement with those obtained from NLRHA, thus demonstrating the adequacy of the FR-RSA method for the analysis of bridge structures crossing strike-slip faults.